The effects of bungeeskate training on measures of on-ice acceleration and speed - Janot, J. M.; Auner, K. A.; Emberts, T. M.; Kaatz, R. M.; Matteson, K. M.; Muller, E. A.; Cook, M. (International Journal of Sports Physiology and Performance, 2013)
Further research has demonstrated that off-ice horizontal training (sled pull, parachute, etc) relates well to on-ice acceleration and speed. However, there is limited literature pertaining to on-ice resistance training that aims to enhance speed and acceleration in hockey players. The purpose of the current study was to determine if on-ice BungeeSkate training would improve on-ice speed and acceleration in youth hockey players. Methods: Twenty-three Peewee and Bantam hockey players (age 11-14) were recruited, with 20 participants completing the study. Pretesting and posttesting consisted of an on-ice 44.8-m speed test, a 6.1-m acceleration test, and a 15.2-m full-speed test. The training protocol consisted of 8 sessions of 5 BungeeSkate training exercises per session, 2 times per week for a 4-wk period. Results: The results of this study showed that speed and top speed were significantly increased (P < .05) by 4.2% and 4.3%, respectively. Acceleration was also slightly improved but not significantly. Conclusions: A 4-wk BungeeSkate training intervention can improve acceleration and speed in youth hockey players. This training method could be a valid adjunct to existing strategies to improve skill development in hockey and is shown to improve speed and acceleration in relatively short training sessions. This may be most advantageous for hockey coaches and players who are looking to maximize training benefits with limited ice time.